Community garden programme: the volunteers' satisfaction - Ramalingam, Leelanayagi; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin; Ali, Fazlin (Human Resource Management Academic Research Society, 2018)
Urban agriculture that is being practised by 800 million people worldwide is beneficial in term of social, economy and environment. Malaysia is practising urban agriculture due to the role it plays in overcoming the dilemma of food insecurity. Urban agriculture is known as food production activities in cities. Community Garden Programme is a type of Urban Agriculture Programme which is supported by various organisations. The main goal of this paper is to identify the volunteers’ satisfaction level and those who are really satisfied with the Community Garden Programme. Items used to measure volunteers’ satisfaction were adapted from Omoto and Snyder (1995). The survey with 375 volunteers indicated that majority of them were satisfied with the Community Garden Programme. Moreover, elderly males were significantly satisfied with the programme. Hence, approaching elderly male for volunteering in Community Garden Programme may produce fruitful result because highly satisfied volunteers tend to continue with volunteering in the future.